INTERNALISASI NILAI GOTONG ROYONG SISWA KELAS IV SEKOLAH DASAR - Maharani, Perdita Winola; Asriyanti, Frita Devi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The value of mutual cooperation is one of the values of Pancasila that reflects an attitude of cooperation, mutual assistance, caring, and shared responsibility. It is important to instill this value starting in elementary school because it plays a role in shaping students’ social character. The internalization of the value of mutual cooperation can be achieved through various learning activities that involve interaction and cooperation among students. This study aims to describe the internalization of the value of mutual cooperation among fourth-grade students at SDN 1 Jepun in Tulungagung Regency. This study employs a qualitative approach using a phenomenological methodology. Research data were collected through observation, interviews, and documentation. The results indicate that the value of mutual cooperation has been internalized in the learning process of fourth-grade students. This value is evident in their willingness to help peers experiencing learning difficulties, their concern for classmates, their mutual respect during discussions, and their ability to collaborate in completing group assignments. The students also demonstrated responsibility toward the assigned tasks and actively participated in group activities. Although there are still some students who are not yet consistent in applying the value of mutual cooperation, in general, this value has become an integral part of the students’ behavior during learning activities. Based on the research findings, it can be concluded that the value of mutual cooperation has been well internalized by the fourth-grade students at SDN 1 Jepun in Tulungangung Regency.